Attitudes towards immigrants, other integration barriers, and their veracity - Amelie F. Constant; Martin Kahanec; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The paper studies opinions and attitudes towards immigrants and minorities and their interactions with other barriers to minorities' economic integration. Specifically, we consider the minority experts' own perceptions about these issues, the veracities and repercussions of unfavorable attitudes of natives. Employing newly available data from the IZA Expert Opinion Survey 2007 we depict main trends in the integration situation of ethnic minorities in Europe in a comparative manner. Using a unique dataset, this innovative study is the first to gauge the perspectives of expert stakeholders and ethnic minorities on their integration situation and the main barriers that hinder it. Robust findings show that ethnic minorities: face integration problems; natives' general negative attitudes are a key factor of their challenging situation; discrimination is acknowledged as the single most important integration barrier; low education and self-confidence as well as cultural differences also hinder integration; minorities want change and that it come about by policies based on the principle of equal treatment. Well designed integration policies that take the specific situation of the respective ethnic minority into account, are persistent and enforce anti-discrimination laws are desirable.
Keywords: J15; J71; J78; 330; Attitudes; opinions; immigrants; ethnic minorities; labor market; Migranten; Sachverständige; Meinung; Ethnische Diskriminierung; Soziale Integration; Berufliche Integration; Migrationspolitik; EU-Staaten